1982
DOI: 10.1017/s0022172400069953
|View full text |Cite
|
Sign up to set email alerts
|

The effect of time in lairage on the frequency of salmonella infection in slaughtered pigs

Abstract: SUMMARYGroups of pigs were brought to an abattoir by truck and approximately 25 were killed on each of the next 3 days.While the pigs were in lairage they were given water but were not fed. After slaughter the caecal contents of all pigs were cultured to detect Salmonella spp.The organism was isolated from 70 % of 145 pigs killed after 1 day in lairage, 49 % of 143 pigs that had been in lairage for 2 days and 41 % of 135 pigs that had been held for 3 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
11
1
Order By: Relevance
“…It has been reported that pork carcass contamination with Salmonella enterica is primarily related to intestinal S. enterica infections (4,16,23). It is assumed that the more S. enterica that is carried into the slaughter process, via the pig's intestines, the greater the risk of equipment and final product contamination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that pork carcass contamination with Salmonella enterica is primarily related to intestinal S. enterica infections (4,16,23). It is assumed that the more S. enterica that is carried into the slaughter process, via the pig's intestines, the greater the risk of equipment and final product contamination.…”
mentioning
confidence: 99%
“…One possibility for this increase in isolation rates is long-term lairage (greater than 12 h) in contaminated abattoir holding pens (4,9,13,14,16). In the United States, most abattoirs report that they try to avoid holding pigs for more than 6 to 8 h. However, a 2-h holding period is recommended to improve meat quality (2,8,22).…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6] This increase in prevalence has been attributed to the effects of stress on immunity, increased mingling of pigs, and recurrence of shedding. [1][2][3][4][5][6] This increase in prevalence has been attributed to the effects of stress on immunity, increased mingling of pigs, and recurrence of shedding.…”
mentioning
confidence: 99%
“…Nattress and Murray (2000) showed an increase in cecal coliform numbers with the increase of feed withdrawal times from 0 to 15 h and with lairage times ranging from 1 to 5 h. Other studies reported that the longer the time spent by the pigs in the lairage, the higher the cecal contamination and Salmonella shedding (Craven and Hurst, 1982;Morgan et al, 1987;Hurd et al, 2002).…”
Section: Effect On Cecal Microbial Populationsmentioning
confidence: 98%